Genesis of life from the matter dynamic process - Núñez De Castro, Ignacio (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Biology does not deal with life, but the phenomenological description of living beings; the life study belongs to the Natural Philosophy. For a coherent discussion in order to learn what a living being is, several categories as: holistic comprehension, system, process, novelty emergence, teleology, epigenesis and evolution are needed. In this way a different rationality, non-mechanicist, may be constructed. The systemic thought is always a process thought. Therefore, the process philosophy is good tool for understanding the living organisms. Reality is not static, but dynamic; we must pass from the substance (being) metaphysics, to that of becoming. The novelty emergence is achieved from the complexity. The system explanation is not found in the elements (analysis), but in the hierarchical organization of the system as a whole, which has an internal teleology. Genome, which is epigenetically developing, is the program that bases the structure and performances of organisms. The elemental analysis unit for microorganisms, vegetables and animals, the cell, is a dynamic unity always in the process of mitosis. Time scale is essential for the understanding of living organisms; if the living being’s series is observed in big time periods, we conclude that to live is to be in development and nothing in Biology has meaning, but in the light of evolution.
Keywords: Biology; Natural Philosophy; life; living being; systemic thought; process; emergence; teleology; epigenesis; evolution